PENERAPAN NASH EQUILIBRIUM DAN STRATEGI DOMINAN DALAM PERSAINGAN XL AXIATA DAN INDOSAT OOREDOO HUTCHISON - Hamzah Putra; Kharisma Hanum Intan Maharani; Putri Zahra Ayu Zahira; Rachell Davina; Salwa Azizah (Veteran Economics, Management, & Accounting Review, 2025)
This study analyzes the application of Nash Equilibrium and dominant strategy in price and service competition between two major telecommunication companies in Indonesia, XL Axiata and Indosat Ooredoo Hutchison. Using literature review methods, this research aims to understand how the two companies interact in an oligopoly market, as well as how their strategic decisions affect market structure and consumer welfare. The analysis is based on secondary data collected from scientific journals, web articles, and industry reports, which are then used to model price competition through a game-theoretic approach. The results show that in the context of data plan price competition, Nash Equilibrium is reached when both firms set low prices, although this strategy may reduce long-term profitability. In addition, no dominant strategy was found that always provides maximum profit for either firm without considering the actions of competitors. Keywords: Nash Equilibrium, Price Competition, Dominant Strategy   Abstrak  Penelitian ini menganalisis penerapan Nash Equilibrium dan strategi dominan dalam persaingan harga dan layanan antara dua perusahaan telekomunikasi besar di Indonesia, XL Axiata dan Indosat Ooredoo Hutchison. Dengan menggunakan metode studi literatur yang dilakukan berdasarkan data sekunder yang dikumpulkan dari jurnal ilmiah, artikel web, dan laporan industri, yang kemudian digunakan untuk memodelkan persaingan harga melalui pendekatan teori permainan. Hasil penelitian menunjukkan bahwa dalam konteks persaingan harga paket data, Nash Equilibrium tercapai ketika kedua perusahaan menetapkan harga rendah, meskipun strategi ini dapat mengurangi profitabilitas jangka panjang. Selain itu, tidak ditemukan strategi dominan yang selalu memberikan keuntungan maksimal bagi salah satu perusahaan tanpa mempertimbangkan tindakan pesaing.  Kata Kunci: Nash Equilibrium, Persaingan Harga, Strategi Dominan